EFFECT OF PROFITABILITY, LEVERAGE AND CHARACTERISTICS OF CORPORATE GOVERNANCE IN TAX AVOIDANCE MINING COMPANY LISTED IN BEI - Anita Wijayanti, Andhika Avistra Rahmawati, Endang Masitoh W & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aimed to examine the effect of profitability, leverage, and corporate governancecharacteristics against tax avoidance on mining companies listed on the Indonesia StockExchange in 2013-2015. The independent variables in this study are Return on Assets(ROA), Dept to Equity Ratio (DER), institutional ownership, independent board and auditcommittee. While the dependent variable in this study is tax avoidance by using CashEffective Tax Rate (CETR). The sampling technique is done by using purposive samplingmethod and data analysis tool used is multiple linear analysis. The sample used in this studyis that mining companies listed on the Indonesia Stock Exchange in the period 2013-2015,with a total of 11 companies per period. The results of this study concluded that the variableReturn On Assets and Dept. To Equity Ratio effect on tax avoidance in mining companies,whereas the institutional ownership variable, independent board and audit committee doesnot affect the tax avoidance in mining companies.Keywords: Profitability, leverage, corporate governance, tax avoidance